2023
DOI: 10.1177/03635465231181059
|View full text |Cite
|
Sign up to set email alerts
|

Screws or Sutures? A Pediatric Cadaveric Study of Tibial Spine Fracture Repairs

Thomas M. Johnstone,
David W. Baird,
Annelisse Cuellar-Montes
et al.

Abstract: Background: Tibial spine fractures are common in the pediatric population because of the biomechanical properties of children’s subchondral epiphyseal bone. Most studies in porcine or adult human bone suggest that suture fixation performs better than screw fixation, but these tissues may be poor surrogates for pediatric bone. No previous study has evaluated fixation methods in human pediatric knees. Purpose: To quantify the biomechanical properties of 2-screw and 2-suture repair of tibial spine fracture in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In a biomechanical meta-analysis, no significant difference was found between suture and screw fixations in terms of stiffness and displacement after cyclic testing in adults. 33 In the only biomechanical study conducted for children, Johnstone et al 10 recently showed that suture and screw fixations of TEFs in pediatric human cadavers were biomechanically similar. Additionally, those authors found that pediatric bone fails at lower loads compared with adult cadaveric bone and porcine bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a biomechanical meta-analysis, no significant difference was found between suture and screw fixations in terms of stiffness and displacement after cyclic testing in adults. 33 In the only biomechanical study conducted for children, Johnstone et al 10 recently showed that suture and screw fixations of TEFs in pediatric human cadavers were biomechanically similar. Additionally, those authors found that pediatric bone fails at lower loads compared with adult cadaveric bone and porcine bone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those authors found that pediatric bone fails at lower loads compared with adult cadaveric bone and porcine bone. 10 Given the low ultimate failure loads observed for both suture and screw fixation methods in pediatric specimens, the postoperative rehabilitation program for children should differ from that in adults. In the present study, a full extension knee brace was used, with no knee movement allowed for 2 weeks postoperatively, and weightbearing was restricted until the end of the fourth postoperative week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the above study specimens were not representative of the characteristics of children's skeleton, Johnstone et al ( 38 ) matched the age and side of 12 knees from 6 children's cadavers, and divided them into a double screw group and the suture group, in which the double screw group was fixed with two 4 mm × 35 mm partially threaded cannulated screws, and the suture group was fixed with two No. 2 FiberWire sutures through the anterior 1/3 and posterior 1/3 of the cruciate ligament, and then pulled through the bone tunnels on the medial and lateral side of the fracture fragment to be knotted and fixed outside the joint.…”
Section: Comparison Of Different Fixation Techniquesmentioning
confidence: 99%
“…The arthroscopic reduction and internal fixation techniques can use a variety of fixation methods, such as metal screws [ 10 ], sutures [ 11 13 ], and suture anchors [ 14 ]. Of these methods, most biomechanical studies of porcine or human bone show that suture fixation is superior to screw fixation [ 15 ]. Although there are various biochemical comparative studies of arthroscopic tibial eminence fracture fixation methods, the best choice of technique remains controversial [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%